Sarcasm in Lauren Weisberger Film "The Devil Wears Prada 1" - Fardan Maulana; Humaira Qashwa; Mulidya Septriwan Callista; Aulia Salsabilla; Syamsul Bahri (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
The use of language in literature and film plays an important role in expressing ideas, emotions and also in criticism. The film The Devil Wears Prada contains many sarcastic types, especially in a conversation between the main characters in the competitive fashion industry. The characters frequently use sarcastic language to criticize something around them. These sarcasm is not only to create drama and humor but also reflect work pressure. This research analyzes the use of the sarcasm in the movie The Devil Wears Prada that made by Lauren Weisberger by using Elizabeth Camp (2012) theory about sarcasm. Purpose of this study to identify type of sarcasm and explain how it reflects criticism and implicit meaning in the films. This research uses a descriptive qualitative method because this study focuses on the dialog meaning based on the context. The primary data of this study are the dialog and movie script taken from the film. The findings show that there are 21 sarcasms found in this film. Propositional sarcasm appears most frequently with 13 data followed by lexical sarcasm with 5 data, illocutionary with 3 data while Like-Prefixed Sarcasm with 0 data. The results show that propositional sarcasm becomes the dominant type because the characters often express criticism and negative directly through statements.